Evaluation of the Antioxidant Activity of the Flavonoids Isolated from Heliotropium Sinuatum Resin Using Oracfl, Dpph and Esr Methodologies - Modak-Canobra, B; Barriga-Gonzalez, G; Salinas-Quezada, M (Sociedad Chilena de Quimica, 2016)
The antioxidant capacity has been determined for a number of flavonoid compounds from Heliotropium sinuatum, a plant that grows in arid areas in the north of Chile. The methodologies used were: ORACFL (oxygen radical absorbance capacity - fluorescein), DPPH (2,2-diphenyl-2-picrylhydrazyl) bleaching and electron spin resonance (ESR). These compounds were studied in homogeneous and heterogeneous media. The results showed that the 7-o-methyleriodictiol and 3-o-methylisorhamnetin are those with the highest antioxidant capacity. © 2016, Sociedad Chilena de Quimica. All rights reserved.